Narečne prvine v evangeličanskem Düševnem listu - Koletnik, Mihaela (Slavia Centralis, 2020)
Dialect features in the evangelical newspaper Düševni list The present paper reflects upon dialect characteristics in the monthly newspaper Düševni list (1922–1941) with which the Prekmurje Evangelicals realised the idea of having a religious publication of their own. Although Düševni list began publication in a time when the regional standard language varieties had already unified with the central Slovene one, the editors of Düševni list made great efforts to remain loyal to the Protestant language tradition of Štefan Küzmič and thus a tongue close to the dialect spoken by Protestant worshipers living on the territory between the rivers Mura and Raba. From the first half of the18th Century on, the Prekmurian books were written in the Prekmurian script. The same is true of Düševni list in the period from 20 December 1922 until 20 November 1931. On 20 December 1931, however, Gaj’s Latin alphabet was introduced. It replaced the Bohorič alphabet used in the central Slovene language territory until then and was, from the mid-19th Century on, adopted by the Prekmurian Catholic authors as well.